The presence of diabetic retinopathy closely associated with the progression of non-alcoholic fatty liver disease: A meta-analysis of observational studies - Zhang, Guo-heng; Yuan, Tian-hao; Yue, Zhen-sheng; Wang, Lin; Dou, Guo-Rui (Frontiers in Molecular Biosciences, 2022)
Background and Objective: There is growing evidence that non-alcoholic fatty liver disease is related to diabetic retinopathy, but research results are variant. Therefore, we conducted a meta-analysis to assess the association between the progression non-alcoholic fatty liver disease and the onset of diabetic retinopathy. Methods: PubMed, Embase, and Cochrane databases were searched until November 7, 2021. Combined odds ratios and 95% confidence intervals were used to assess the association. Results: We identified 18 studies involving 12,757 patients by retrieval. The pooled effect assessment showed that liver fibrosis was positively correlated with diabetic retinopathy (OR=1.69, 95%CI 1.30-2.20; P < 0.0001); non-alcoholic fatty liver disease was not associated with the risk of diabetic retinopathy (OR=1.15, 95%CI 0.75-1.76; P = 0.51); Non-alcoholic fatty liver disease was positively correlated with DR in patients with type 1 diabetes (OR=2.96, 95%CI 1.48-5.94; P = 0.002); In patients with type 2 diabetes, there was no association (OR=0.92, 95%CI 0.59 to 1.43; P = 0.70). Subgroup analysis showed no correlation in both Asian and Caucasian races. Conclusion: Liver fibrosis significantly increases the risk of diabetic retinopathy in diabetic patients. This suggests that the ocular examination of diabetic retinopathy could be helpful to determine whether patients with nonalcoholic fatty liver disease would progress to liver fibrosis.